PONDx: real-life utilization and decision impact of the 21-gene assay on clinical practice in Italy - Francesco Cognetti (Nature Portfolio, 2021)
Abstract Clinicopathological prognostic features have limited value to identify with precision newly diagnosed patients with hormone receptor (HR)-positive, HER2-negative breast cancer (BC), who would benefit from chemotherapy (CT) in addition to adjuvant hormonal therapy (HT). The 21-gene Oncotype DX Breast Recurrence Score® (RS) assay has been demonstrated to predict CT benefit, hence supporting personalized decisions on adjuvant CT. The multicenter, prospective, observational study PONDx investigated the real-life use of RS® results in Italy and its impact on treatment decisions. Physicians’ treatment recommendations (HT ± CT) were documented before and after availability of RS results, and changes in recommendations were determined. In the HR+ HER2− early BC population studied (N = 1738), physicians recommended CT + HT in 49% of patients pre-RS. RS-guided treatment decisions resulted in 36% reduction of CT recommendations. PONDx confirms that RS results provide clinically relevant information for CT recommendation in early-stage BC, resulting in a reduction of more than a third of CT use.